2009 International Conference on Electrical Machines and Systems 2009
DOI: 10.1109/icems.2009.5382860
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of MRAS based induction motor sensorless vector control system taking into account iron loss

Abstract: We have proposed a current observer-based speed sensorless vector control system taking into account both iron loss and stator resistance identification. The method is constructed in a synchronously rotating reference frame. The effectiveness of the proposed system has been investigated by digital simulation and experimentation. Furthermore important control parameters such as stator resistance, observer gain and filter of speed estimation are studied by comparing the computed result with experimental one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Online tuning of R s and/or R r is reported in previous studies, 5,[11][12][13] compensation of magnetic saturation, 2,5,[13][14][15] and compensation of iron losses. 5,11,13,14,16 In, Baši c et al, 14 an MRAS scheme is proposed which includes compensation of magnetic saturation, stray-load, and iron losses. It has been further upgraded in Baši c et al 5,13 with a full parameter tuning mechanism (i.e., online adaptation of stator resistance, rotor resistance, stray-load resistance, magnetizing inductance, and iron loss resistance).…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…Online tuning of R s and/or R r is reported in previous studies, 5,[11][12][13] compensation of magnetic saturation, 2,5,[13][14][15] and compensation of iron losses. 5,11,13,14,16 In, Baši c et al, 14 an MRAS scheme is proposed which includes compensation of magnetic saturation, stray-load, and iron losses. It has been further upgraded in Baši c et al 5,13 with a full parameter tuning mechanism (i.e., online adaptation of stator resistance, rotor resistance, stray-load resistance, magnetizing inductance, and iron loss resistance).…”
Section: Introductionmentioning
confidence: 63%
“…Among MBEs, model reference adaptive system (MRAS) and sliding mode observers (SMOs) are more practical in common engineering applications and are attracting more and more attention. 2,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] They are both designed on the basis of the IM dynamic mathematical model. The accuracy of the estimated speed strongly depends on the accuracy with which the utilized IM model describes the real IM behavior.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations for MRAS based sensorless control of induction machines in [4], [5] showed that the iron losses cause speed estimation errors which are of the same order as other parameter variation effects. In [6], [7] also the resulting torque error is analysed which would occur, if the iron losses were not considered in the speed sensorless vector control system of induction motors. In contrast to induction machines no speed estimation but a position estimation error occurs by reason of the iron losses for back-EMF based sensorless control of PMSM.…”
Section: Introductionmentioning
confidence: 99%